PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PERUSAHAAN SUB SEKTOR FARMASI YANG ADA DI BEI - Fariq Hizba; Nurjanti Takarini (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This study aims to analyze the influence of financial ratios with dividend policy as a moderation toward changes in pharmaceutical stock prices listed on the Indonesia Stock Exchange (IDX) during the period of 2020-2023. This research uses a quantitative associative approach to determine the cause-and-effect relationship between variables. Data collection techniques use secondary data from financial statements and historical data of pharmaceutical companies listed on the IDX. The sample determination in this study uses purposive sampling, which resulted in 8 sample companies. The type of data is panel data, which is a combination of cross-sectional and time series data. The variables used in this study are Profitability (ROE), Liquidity (CR), Dividend Policy (DPR), and Stock Price. To analyze the data, Moderated Regression Analysis (MRA) is used through the SPSS application to test the hypothesis. The results of the hypothesis test show that ROE has a significant positive effect on stock prices, CR has no effect on stock prices, DPR weakens the effect of ROE on stock prices, and DPR strengthens the effect of CR on stock prices.